Early identification of palliative care needs by family physicians: A qualitative study of barriers and facilitators from the perspective of family physicians, community nurses, and patients. (June 2014) - Beernaert, Kim; Deliens, Luc; De Vleminck, Aline; Devroey, Dirk; Pardon, Koen; Van den Block, Lieve; Cohen, Joachim
Background: There is a growing recognition that a palliative care approach should be initiated early and not just in the terminal phase for patients with life-limiting diseases. Family physicians then play a central role in identifying and managing palliative care needs, but appear to not identify them accurately or in a timely manner. Aim: To explore the barriers to and facilitators of the early identification by family physicians of the palliative care needs. Design, setting, and participants: Six focus groups (four with family physicians, n = 20, and two with community nurses, n = 12) and 18 interviews with patients with cancer, chronic obstructive pulmonary disease, heart failure, and dementia were held. Thematic analysis was used to derive themes that covered barriers and facilitators. Results: Key barriers and facilitators found relate to communication styles, the perceived role of a family physician, and continuity of care. Family physicians do not systematically assess non-acute care needs, and patients do not mention them or try to mask them from the family physician. This is embedded within a predominant perception among patients, nurses, and family physicians of the family physician as the person to appeal to in acute and standard follow-up situations rather than for palliative care needs. Family physicians also seemed to pay more often attention to palliative care needs of patients in a terminal phase. Conclusion: The current practice of palliative care in Belgium is far from the presently considered ideal palliative care approaches. Facilitators such as proactive communication and communication tools could contribute to the development of guidelines for family physicians and policymakers in primary care.